Comprehensive modeling of the extrinsic transconductance for InxGa1-xAs/In0.52Al0.48As quantum-well high-electron-mobility transistors. (December 2022) - Yun, Seung-Won; Jo, Hyeon-Bhin; Jeong, Hyeon-Seok; Park, Wan-Soo; Yoo, Ji-Hoon; Lee, In-Geun; Kim, Tae-Woo; Tsutsumi, Takuya; Sugiyama, Hiroki; Matsuzaki, Hideaki; Kim, Dae-Hyun
Abstract: This paper presents the comprehensive modeling of extrinsic transconductance ( gm_ext ) in the saturation regime for In x Ga 1-x As/In 0.52 Al 0.48 As quantum-well (QW) high-electron-mobility transistors (HEMTs) with Lg from 10 μm to sub-100 nm, covering the ballistic and mobility relevant regimes. First, we fabricated and characterized two types of lattice matched (LM) channel In 0.53 Ga 0.47 As QW HEMTs on a 3-inch InP substrate. One of these was fully fabricated with an i -line stepper, yielding Lg from 10 μm to 0.5 μm, and the other was fabricated in a mix & match manner with a combination of an i -line stepper and an e-beam lithography equipment, where T -shaped gates were implemented using a tri-layer resist stack of ZEP520A-PMGI-ZEP520A in the e-beam lithography process. Using devices with a wide range of Lg values, we examined the transconductance ( gm ) characteristics in saturation and attempted to correlate them to analytical expressions capable of describing the carrier transport properties of the devices using only physical parameters, such as the gate capacitance ( Cgi ) apparent mobility (μ n_app ), and saturation velocity ( vsat ), and the series resistances ( Rs and Rd ). In this way, we assessed the dependences of the extrinsic transconductances of the fabricated devices on their gate lengths, with the model parameters of Cgi  = 0.65 μF/cm 2, μ n_app  = 9400 cm 2 /V⋅s, vsat  = 4.3 × 10 7 cm/s and Rs  = 147 Ω⋅μm. These values were observed to be well-matched with those of the physical parameters. Most importantly, we extended the proposed approach to realistically project the increase in gm_ext that could be accomplished by improving certain device parameters.